Physicochemical Properties and Low-Temperature Sulfur Fixation Patterns of Fly Ash from a Biomass Power Plant - Jun Zhang; Peng Zhang; Jie Zhou; Bo Zhao; Ansheng Wei; Liqiang Zhang (Energies)
Biomass power plants generate a vast amount of biomass ash (BA) and release sulfur dioxide (SO2) and other pollutants. In this study, a new idea of flue gas desulfurization (FGD) using BA was proposed for biomass power plants. The physicochemical properties, surface morphology, and microstructure of fly ash generated by a typical biomass power plant in the Shandong area of China were characterized using X-ray fluorescence spectrometry (XRF), X-ray diffraction (XRD), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDS). The results indicated that the BA contained alkaline-providing metal oxides, including alkali metal oxides (K2O at 7.57% and Na2O at 1.47%) and alkaline earth metal oxides (CaO at 10.52% and MgO at 4.52%). SiO2 constituted the primary crystalline phase, while KCl, CaCO3, and CaSiO3 phases were also identified. BA has diverse morphological characteristics, including irregular angular/acicular, spherical, and flocculent-shaped particles, among which the flocculent-shaped particles were mainly the calcium oxide (CaO)-containing composite of alkaline earth metal oxides and quartz. The potential of BA to absorb SO2 is attributable to CaO and other alkaline substances. The desulfurization experiment indicated that humidified BA allows for an effective FGD process that generates flaky crystalline solids of calcium sulfate (CaSO4). Therefore, this method utilizes the alkalinity of BA for FGD in biomass power plants.